Recessive MYF5 Mutations Cause External Ophthalmoplegia, Rib, and Vertebral Anomalies - ELÇİOĞLU, HURİYE NURSEL (CELL PRESS, 2018)
MYF5 is member of the Myc-like basic helix-loop-helix transcription factor family and, in cooperation with other myogenic regulatory factors MYOD and MYF5, is a key regulator of early stages of myogenesis. Here, we report three consanguineous families with biallelic homozygous loss-of-function mutations in MYF5 who define a clinical disorder characterized by congenital ophthalmoplegia with scoliosis and vertebral and rib anomalies. The clinical phenotype overlaps strikingly with that reported in several Myf5 knockout mouse models. Affected members of two families share a haploidentical region that contains a homozygous 10 by frameshift mutation in exon 1 of MYF5 (c.23_32delAGTTCTCACC [p.GIn8Leufs*86]) predicted to undergo nonsense-mediated decay. Affected members of the third family harbor a homozygous missense change in exon 1 of MYF5 (c.283C>T [p.Arg95Cys]). Using in vitro assays, we show that this missense mutation acts as a loss-of-function allele by impairing MYF5 DNA binding and nuclear localization. We performed whole-genome sequencing in one affected individual with the frameshift mutation and did not identify additional rare variants in the haploidentical region that might account for differences in severity among the families. These data support the direct role of MYF5 in rib, spine, and extraocular muscle formation in humans.
Keywords: BASIC DOMAIN; PROTEIN; MYOD; SPECIFICATION; EXPRESSION; DISORDERS; BINDING